Political Communication of Hasan Basri Agus; Dramaturgical Analysis in Jambi Local Government Implementation - Ahmad Harun Yahya (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2019)
Hasan Basri Agus was the winner of the Jambi local election in 2010. Start his career from civil servant, and then became head of subdistrict before he was choosen as regent of Sarolangun and the last he was elected as Jambi governor in the period of 2010-2015. In the applied of his government, Hasan Basri Agus applied the principles of political communication as an important way to build interaction relationship with Jambi communities. The research uses a qualitative method by using a constructive paradigm. Based on constructive paradigm, the next approach the researcher use in a dramaturgical analysis. This research sought to give an objective analysis of the political communication of the Jambi Governor in the applied of his government. The result of the research show that Hasan Basri Agus succesfully represented him self as people protector, religious, and charismatic leader.